IMPLEMENTATION OF COTELBAPAI PHYSICS E-MODULE TO IMPROVE STUDENTS’ SCIENTIFIC LITERACY AND PHYSICS IDENTITY (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2026)
This study examines the integration of local wisdom and artificial intelligence (AI) in physics learning media using bakpia, a traditional Indonesian food, as the learning context. The study aims to determine the effectiveness of the COTELBAPAI E-module and to analyze the profile distribution of students’ scientific literacy and physics identity. A quasi-experimental method with an equivalent control group design was employed, involving 108 eleventh-grade students from SMAN 2 Banguntapan, divided into one experimental class and two control classes. Data were collected using test and questionnaire instruments. The results indicate that the COTELBAPAI E-module is highly effective in enhancing students’ scientific literacy and physics identity. This is evidenced by a large effect size (3.017), with a 57.6% increase in students achieving very high scientific literacy, and an exceptionally large effect size (Cohen’s d = 8.872), with a 76.7% increase in students categorized as having very strong physics identity. The novelty of this study lies in the integration of the Contextual Teaching and Learning (CTL) approach, artificial intelligence, and local wisdom within a single E-module, as well as the simultaneous evaluation of scientific literacy and physics identity. These findings provide empirical evidence that AI-assisted, context-based learning grounded in local culture can strengthen students’ physics identity. However, the generalizability of the results is limited by the sample size and implementation duration.